1991
DOI: 10.1007/bf00179037
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of electrical stimulation, blockade of neuronal amine uptake and activation of α2-adrenoceptors on the release of endogenous noradrenaline and 5-hydroxytryptamine from the isolated rat pineal gland

Abstract: Isolated rat pineal glands were incubated in vitro and the release of endogenous noradrenaline or 5-hydroxytryptamine (5-HT) and 5-hydroxyindoleacetic acid (5-HIAA) was determined by HPLC with electrochemical detection. In the absence of test drugs, the spontaneous outflow of noradrenaline was about 10 fmol/10 min and electrical stimulation (5 Hz, 1500 pulses) evoked the release of about 70 fmol noradrenaline. Nomifensine enhanced the spontaneous outflow of noradrenaline about threefold and the electrically ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
2
4
1
Order By: Relevance
“…After this time, 5-HT and 5-HIAA output showed a progressive decrease of approximately 5-8% per h. Similar biphasic secretory patterns of indoleamine secretion from perifused pineal glands were previously reported ( 10,34). Indoleamine secretory profiles obtained by incubating pineal glands removed from SCGx rats run in parallel with those taken from control pineal glands.…”
Section: Spontaneous Release Of S-ht and 5-hiaa From Intact And Scgx supporting
confidence: 66%
See 1 more Smart Citation
“…After this time, 5-HT and 5-HIAA output showed a progressive decrease of approximately 5-8% per h. Similar biphasic secretory patterns of indoleamine secretion from perifused pineal glands were previously reported ( 10,34). Indoleamine secretory profiles obtained by incubating pineal glands removed from SCGx rats run in parallel with those taken from control pineal glands.…”
Section: Spontaneous Release Of S-ht and 5-hiaa From Intact And Scgx supporting
confidence: 66%
“…Recently it has been reported that the release of 5-HT from the pineal gland is calciumindependent and increases in presence of L-tryptophan, suggesting a preferential efflux of newly synthesized 5-HT (34). In our study, release of 5-HT is likely to occur in absence of de novo 5-HT synthesis, since the lack of tryptophan in the medium.…”
Section: Discussionmentioning
confidence: 47%
“…The interesting possibility that other mechanisms of 5HT deamination exist was recently suggested by Murphy et al (1990) who reported normal levels of urinary 5HIAA in two individuals with Norrie disease which includes a chromosomal deletion of the gene encoding both MAO enzymes. 5HT catabolism by the pinealocyte is consistent with two observations: 1) electrical stimulation with and without the amine uptake inhibitor nomifensine, which enhanced NE release from nerve terminals, did not alter 5HT and 5HIAA release in vitro (Racke et al, 1991); and 2) the high positive correlation of 5HIAA vs 5HT was further enhanced in individual pineal glands during the rapid increase in 5HT following acute light exposure at night (McNulty et al, 1986). If 5HT was shuttled from the pinealocyte and deaminated in a second cellular compartment during this short period (1-30 min), the correlation of 5HIAA vs 5HT would be expected to decrease rather than increase because of the time lag in making the 5HT accessible to the MAO enzyme.…”
Section: Discussionsupporting
confidence: 89%
“…First, significant levels of the oxidative metabolite 5-hydroxyindole acetic acid (5HIAA) were reported in the pineal gland following removal of the NE terminals by superior cervical sympathectomy (Vassilieff et al, 1982;McIntyre et al, 1985). Second, administration of the neuronal amine uptake blocker nomifensine enhanced release of NE, but did not significantly affect outflow of 5HIAA from the cultured pineal gland (Racke et al, 1991). Finally, the ratio of 5HIAA/5HT exhibited a very high correlation in individual glands during rapid metabolic changes (1-10 min) that occur following acute light exposure during darkness (McNulty et al, 1986) suggesting a single compartment for both substrate and enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Pineal 5-HT release has been found to increase in the presence of NE, which probably acts through a-adrenoceptor mechanisms [Benson et al, 1986;Aloyo and Walker, 1987, 19881. However, the role of the P-adrenergic receptors remains controversial [Aloyo and Walker, 1988;Racke et al, 1991;Olcese and Munker, 19941. Recent studies, indeed, indicate that pineal extracellular 5-HT may interact to modulate the P-adrenergically-induced NAT activity [Sugden, 1990;Olcese and Munker, 19941, sug-gesting that 5-HT may play an autocrine role in the pineal gland.…”
Section: Introductionmentioning
confidence: 99%